2022
DOI: 10.3389/fpubh.2022.1061796
|View full text |Cite
|
Sign up to set email alerts
|

Parents' pandemic stress, parental involvement, and family quality of life for children with autism

Abstract: BackgroundResearch has shown that parents of children with autism spectrum disorder (ASD) suffered high levels of stress during the COVID-19 pandemic and faced poor family quality of life (FQOL). However, little is known about the inherent dynamic interaction between pandemic stress and FQOL, especially in the Chinese cultural context.AimsThis study provides preliminary evidence by examining the relationships among pandemic stress, parental involvement, and FQOL for children with autism in mainland China.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Raising the level of pragmatic hopefulness among parents of autistic children requires the attention and support of the government and society. On the one hand, schools and medical institutions should help families of autistic children to establish rational and optimistic perceptions about the pandemic, learn to self-regulate during the special period, and use their resources rationally ( 5 , 61 ). On the other hand, public health departments should conduct a series of courses and lectures related to the pandemic to help parents of autistic children acquire knowledge about the pandemic’s impact on their health and their children’s development ( 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Raising the level of pragmatic hopefulness among parents of autistic children requires the attention and support of the government and society. On the one hand, schools and medical institutions should help families of autistic children to establish rational and optimistic perceptions about the pandemic, learn to self-regulate during the special period, and use their resources rationally ( 5 , 61 ). On the other hand, public health departments should conduct a series of courses and lectures related to the pandemic to help parents of autistic children acquire knowledge about the pandemic’s impact on their health and their children’s development ( 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in risk perception and concern was followed by a decrease in parental involvement, which was, in turn, followed by a decrease in parents’ views on their children’s academic and social success. Risk perception and concern about the COVID-19 pandemic risk may have distracted parents of autistic children from being involved in their children’s learning and lives ( 5 ), resulting in lower levels of parental involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These measures have unprecedentedly affected lives and well-being of children with special educational needs and disabilities (SEND) and their families due to disruption of educational support, individualized behavioral interventions, childcare support, or other services and programs (Ziauddeen et al, 2020;Lee et al, 2021). Research has shown that due to the pandemic, parents of children with SEND experienced tremendous challenges trying to balance the demands of meeting educational and socioemotional needs of their children and other family responsibilities, which resulted in increased parenting stress, depression, anxiety and unsatisfactory family quality of life (Asbury et al, 2021;Couper-Kenney and Riddell, 2021;Chen et al, 2022;Sideropoulos et al, 2022;Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%